Uveal Melanoma Metastasis to the Thyroid - Rokshana R. Thanadar; Uzma M. Siddiqui; Shi Bai; Runhua Hou (Case Reports in Endocrinology)
Background. Around 1.2 to 3.1% of thyroid malignancies are due to metastasis. Among them, cutaneous malignant melanomas constitute 4% of malignancy metastasized to the thyroid. Uveal melanoma is uncommon, and its metastasis to the thyroid has only rarely been reported. Hereby, we describe an unusual case of uveal melanoma metastasized to the thyroid and discuss the concept of correct diagnosis. Case Report. During a routine ophthalmological examination, an 86-year-old Caucasian female was found to have retinal detachment secondary to choroidal melanoma. She was treated with gamma knife which resulted in reduction of tumor size. Three months later, she was noted to have a goiter on physical examination. Follow-up thyroid ultrasonography demonstrated numerous vascularized nodules in both lobes. The fine needle aspiration (FNA) of the left dominant nodule was indeterminate the first time and nondiagnostic the second time. FNA of the right dominant nodule was nondiagnostic twice but showed malignant cells the third time. Subsequent immunohistochemistry staining of the FNA sample from the right thyroid nodule confirmed a profile consistent with malignant melanoma. Conclusion. It should be kept in mind that a thyroid nodule detected in a patient with a diagnosis of uveal melanoma can be metastasis and that uveal melanoma diagnosis should be taken into account for the examination of the thyroid tumors of these patients. It is important to employ immunohistochemical staining FNA examination of the patient with such tumors for markers associated with a patient’s known malignancy to facilitate diagnosis.